Optimization of the Use of Bottom Ash PLTSa Bantargebang As an Adsorbent in the Process of Reducing FFA in Used Cooking Oil Biodiesel Raw Material with Taguchi Method: Optimasi Penggunaan Bottom Ash PLTSa Bantargebang Sebagai Adsorben pada Proses Penurunan FFA pada Minyak Jelantah Bahan Baku Biodiesel Dengan Metode Taguchi - Wicaksono, Damar Canggih; Susmiati, Yuana; Prasetyo, Dafit Ari (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2024)
The reduction of FFA levels in used cooking oil as a biodiesel raw material is generally done by the esterification process. Another method that can be used to reduce FFA levels is through the adsorption method. The adsorbent used is bottom ash waste. This study aims to determine the effect of bottom ash adsorbent variation and determine the best variation based on Taguchi analysis. This research uses Taguchi data processing technique with 2 factors and 3 levels. The first factor is adsorbent mass with variations (5% m/v, 10% m/v, and 15% m/v). The second factor is the length of adsorption time with variations (30 minutes, 60 minutes, and 90 minutes). The testing parameters included FFA content, acid number, density, and viscosity. The results of this study were analyzed using the Taguchi method which shows the variation of adsorbent mass and time for FFA content is the variation of 5% m/v adsorbent mass and 30 minutes adsorption time which can reduce FFA by 35.2%, with an acid number value of 3.029 mg KOH/g, density of 0.903 g/cm3 and viscosity of 4.463 sCt in samples that successfully reduced the FFA value by 35.2%.